Levantamento e listagem de procedimentos e influências da alvenaria estrutural - Tambara, Fabiane Steckel (2006)
This work surveys the main procedures and intervenient factors in order to select a constructive technology focusing on structural masonry systems. The listing is simple and easy to analyze; therefore, it proportionates a safe orientation. Besides, the main items which are considered to the introduction of new technologies in companies of civil construction are listed. In addition, the aid theory of decision making is analyzed concerning the technological employment. The research results show criteria that are perceived in a given space-time, therefore, they may vary and modify themselves since they do not express absolute values. Firstly, a questionnaire was applied to managers, engineers and owners of civil construction companies from Santa Maria. The questionnaire was about the choice of this new technology employed, i.e., structural masonry, in order to list the main conditions, benefits and pathologies of this structural system. Based on the diagnosis of both the questionnaire and the bibliographic revision about the aspects related to quality management and competitive strategies, one established a criteria list that should be observed whenever one intends to implant and to select a new technology in the civil construction works. The most relevant criteria concerning new techniques were listed; however, the decisor responsible for selecting the new technique should evaluate the criteria that will be important to a certain undertaking which situates the company in the market. Whatever the chosen alternative, such choice should be based on criteria that assure service to most users needs.